Menopause hormone therapy significantly alters pathophysiological biomarkers of Alzheimer's disease. Issue 4 (15th September 2022) - Depypere, Herman; Vergallo, Andrea; Lemercier, Pablo; Lista, Simone; Benedet, Andrea; Ashton, Nicholas; Cavedo, Enrica; Zetterberg, Henrik; Blennow, Kaj; Vanmechelen, Eugeen; Hampel, Harald; ,
Abstract: Introduction: This increasing body of literature indicates that menopause hormonal replacement therapy (MHT) may substantially mitigate the risk of developing late‐life cognitive decline due to progressive Alzheimer's disease (AD) pathophysiology. For the first time, we investigated the question whether MHT impacts AD biomarker‐informed pathophysiological dynamics in de‐novo diagnosed menopausal women. Methods: We analyzed baseline and longitudinal differences between MHT‐taking and ‐not women in terms of concentrations of core pathophysiological AD plasma biomarkers, validated in symptomatic and cognitively healthy individuals, including biomarkers of (1) the amyloid‐β (Aβ) pathway, (2) tau pathophysiology, (3) neuronal loss, and (4) axonal damage and neurodegeneration. Results: We report a prominent and significant treatment response at the Aβ pathway biomarker level. Women at genetic risk for AD (APOE e4 allele carriers) have particularly shown favorable results from treatment. Discussion: To our knowledge, we present first prospective clinical evidence on effects of MHT on AD pathophysiology during menopause.